PENGARUH BAHASA GAUL TERHADAP PENGGUNAAN BAHASA INDONESIA PADA SISWA SMP NUSANTARA PALANGKARAYA TAHUN 2020 (JURNAL PENDIDIKAN, 2020)
This study aims to describe: 1) the use of slang vocabulary, 2) the use of slang phrases, 3) the effect of the use of slang. This research was conducted in the first semester of the 2019/2020 academic year with 18 students of grade VII and VIII students of SMP Nusantara Palangkaraya. The data collection technique is done by using questionnaire method and direct observation. The results showed: 1) the use of slang vocabulary was mostly used by students to communicate with their friends, 2) the use of slang phrases was sometimes used by students, 3) There was a positive influence on the use of slang